Egyptian government seizes illegal ivory consignments - Esmond Martin (Pachyderm)
In spite of being a party to CITES Egypt has one of the largest retail ivory markets in Africa, as illustrated by the over 21000 ivory carvings observed in retail outlets in Cairo, Luxor and Aswan during the author's 1998 visit. Raw tusks generally come from Sudan, Democratic Republic of Congo and much of the retail sales of worked ivory are to tourists. According to ETIS files the Egyptian government reported no ivory seizures from 1989 to mid 1999, however between September 1999 and April 2000 there were nine seizures comprised of 162 pieces of raw and worked ivory with a total weight of 327 kilograms. The largest seizure was that of 79 raw tusks totally 173 kilograms taken from a Egyptian trader in Aswan.